Financing and governing ecological restoration projects: The Tasmanian Island Ark. (30th December 2021) - Richardson, Benjamin J.; Davidson, Neil J.
Summary: This article examines the financial and governance dimensions of the Tasmanian Island Ark project, in the Tasmanian Midlands. It focuses on the intervention costs, funding sources and the legal context to financing, including property tenure, negotiated agreements and regulatory requirements. The case study shows that it is not easy to extrapolate financial data from one restoration project to another; however, the types of costs, their relative significance and timing, and legal context can be relevant considerations across diverse projects. The Tasmanian case study helps fill a gap in the literature about the financial side of ecological restoration projects and how planners can prepare for large landscape‐scale interventions. The paper discusses the overarching constraints on environmental restoration practices and then presents the specific costs of restoration activities.